2006
DOI: 10.1111/j.1469-1795.2006.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative vulnerability of female turtles to road mortality

Abstract: Recent studies suggest that freshwater turtle populations are becoming increasingly male-biased. A hypothesized cause is a greater vulnerability of female turtles to road mortality. We evaluated this hypothesis by comparing sex ratios from published and unpublished population surveys of turtles conducted on-versus offroads. Among 38 166 turtles from 157 studies reporting sex ratios, we found a consistently larger female fraction in samples from on-roads (61%) than off-roads (41%). We conclude that female turtl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(121 citation statements)
references
References 21 publications
(32 reference statements)
3
114
2
2
Order By: Relevance
“…In the United States, differential mortality of females on roads during nesting migration caused a skewed sex ratio towards males on freshwater turtle populations (e.g. Steen et al 2006). The male-biased sex ratio of P. unifilis in the Guaporé River was also attributed to the lower incubation temperatures and to higher human predation of nests in open, warmer areas, which would produce primarily females (Fachín-Terán and Vogt 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, differential mortality of females on roads during nesting migration caused a skewed sex ratio towards males on freshwater turtle populations (e.g. Steen et al 2006). The male-biased sex ratio of P. unifilis in the Guaporé River was also attributed to the lower incubation temperatures and to higher human predation of nests in open, warmer areas, which would produce primarily females (Fachín-Terán and Vogt 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of a greater sample size, numerous studies have reported biased sex ratios. Differential mortality, distinct behavior, temperature of incubation, different age/size at maturity, sampling methods and microhabitats sampled, are the most mentioned factors to explain a skewed sex ratio (Ream and Ream 1966, Gibbons 1990, Lovich and Gibbons 1990, Steen et al 2006. The male-biased sex ratio commonly reported for Podocnemis spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adults of some species are at elevated risk of death due to predation, desiccation and overheating, harvest by humans, and roadkill during overland movements undertaken to move to more favorable foraging sites, escape unfavorable environmental conditions, migrate to or from hibernacula, or to locate mates (Gibbons, 1986;Buhlmann and Gibbons, 2001). However, mortality of females during nesting migrations and nesting habitat loss may be the most significant threats to freshwater turtle population persistence (Gibbs and Shriver, 2002;Steen et al, 2006). By focusing on life stages that are most at risk and are critical for population persistence and most at risk, we derived information required to generate targets for conservation planning to accommodate the movements of freshwater turtles dictated by their natural history requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, aquatic turtles represent a taxonomic group where a certain life stage (i.e., reproductively active females on terrestrial nesting migrations) is at disproportionate risk of mortality (Steen et al, 2006) and would benefit from terrestrial habitat protections.…”
Section: Introductionmentioning
confidence: 99%
“…When roads act as a barrier to animal movements, populations may become isolated, reducing the gene pool and increasing susceptibility to environmental disturbance and disease. The ability for individuals to travel between subpopulations is the key to genetic diversity and ultimately the survival of the species (Kautz et al 2006, Shilling & Girvetz 2007, Steen et al 2006, Shepard et al 2008, Parris & Schneider 2009). Maintaining and increasing habitat connectivity is already an important need and management goal for wildlife in urban areas and for populations fragmented by roads (Girvetz et al 2008, FitzGibbon et al 2007).…”
Section: Executive Summarymentioning
confidence: 99%